Monitoring Serum Gentamicin Concentration among Newborns in the Neonatal Ward of Hospital Sultan Ismail Petra (HSIP), Malaysia - Abdullah, Adnin; Rahman, Nur Adilah A; Rahman, Rosnani Ab; Awang, Hafizuddin (International Journal of Human and Health Sciences (IJHHS), 2025)
Background: Gentamicin is the empirical therapy of choice for sepsis in newborns, with dosing of 4mg/kg every 24 – 36 hours, depending on premenstrual age. Objective: To investigate the therapeutic drug monitoring (TDM) outcomes (within therapeutic ranges or toxic) of the current IV Gentamicin regimen in treating infections among neonates. Methods: This retrospective cohort study was conducted in Hospital Sultan Ismail Petra (HSIP), between January 2020 and December 2022. Data were abstracted and collected for neonates treated with gentamicin during the study period. Trough and peak levels were measured on the third dose where the therapeutic ranges were <1.0 mg/L and >5.0 mg/L, respectively. Elevated serum creatinine was defined as serum creatinine level (SCr) >71 μmol/L. Multivariable logistic regression was performed to identify the risk factors of acquiring toxic trough levels. Results: A total of 227 patients were included. The total number of patients achieving the targeted peak level was 74.90%. More than half of the patients (52.0%) experienced toxic trough levels. The mean serum trough and peak levels (standard deviation) were 1.23 (1.11) mg/L and 7.31 (3.93) mg/L respectively. The risk factor associated with toxic trough level was elevated SCr (odd ratio 2.55, 95% confidence interval [1.19,5.46], p=0.016). Conclusion: The current gentamicin regimen resulted in an alarming proportion of patients having toxic trough levels, particularly with elevated SCr. The study findings underscore the need to refine the dosing regimen to optimise efficacy and minimise toxicity in neonates. International Journal of Human and Health Sciences Vol. 09 No. 03 Jul’25 Page: 143-150